Theological Stage of Islamic Studies in the West - Aisyah Mawar Octavia; Isa Anshori (Cakrawala: Jurnal Studi Islam, 2021)
Islamic studies is a distinct field of study in the West, particularly in Europe, that is both complex and integral to the larger intellectual current. Even in its early stages, Islamic studies became inextricably linked to political currents in Western countries, giving rise to the term 'orientalism.' The purpose of this research is to consider a variety theological stage that have occurred in the development of Islamic studies in the West. This study reveals that there are three stages in Western-style Islamic studies, namely theological, political, and scientific stages, through a review of the literature. In the West, the study of Islam begins with the paradigm that Islam is a religion that can be studied from any perspective and with such freedom. The issue of dar al-Islam versus dar al-harb, understanding the text and sources of basic and contextual principles, understanding and application of governance Islamic courts (Usul al-Fiqh), the concept of Islam as a universal religion, and ijtihad issues are among the theological issues and Islamic legislation related to the issue of European Muslim identity.